DISTRIBUTION OF DISCOURSE MARKERS ELEMENTS OR DISCOURSE PARTICLE AS AN ENTITY RELATIONSHIP IN DISCOURSE - Sufian Ismail, Anida Sarudin, Zulkifli Osman (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The process of determining groups, features and functions of discourse markers or discourse particle are debateable among language researchers. Various definitions and classification of elements have developed confusion of its status. The efforts to rearrange various opinons related to discourse markers or discourse particles according to certain functions are able to create systematic categories and expose its functions clearly. This article aimed to examine a number of discourse markers concepts or discourse particles and its functions according to the context of grammar and pragmatics as well as the features and domains of discourse markers or discourse particles from views from past studies. The methodology used was the examination of discourse markers or discourse particles into a theory, a model which explained the functions of discourse markers or discourse particles. This explained the research findings which listed the inventory concept of discourse markers or discourse particles, the functions, features and domain of discourse markers or discourse particles in detailed. Distribution of concepts, functions and domain of discourse markers or discourse particles from the views from past studies indicated that discourse markers or discourse particles is a meaningful entity in communication.